DIALEKTIKA SIFAT DAN MAHIYAH TUHAN: Analisis Tahafut At-Tahafut Karya Ibnu Rusyd - Thohari, Afandi; Nur Aziz Thohari, Afandi (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This study examines the dynamics of the debate concerning the divine attributes and mahiyah (essence) of God in Tahāfut al-Tahāfut by Ibn Rushd as a response to al-Ghazālī’s critique in Tahāfut al-Falāsifah. The research employs a descriptive-analytical method with a philosophical approach to explore the encounter between the traditions of kalām and philosophy in understanding the relationship between the Divine Essence and God’s attributes, as well as the concepts of existence (wujūd) and essence (mahiyah) from Ibn Rushd’s perspective. The findings indicate that the differences between theologians and philosophers regarding the divine attributes are fundamentally more conceptual and terminological than substantive in nature. Ibn Rushd maintains that all divine perfections are identical with God’s Essence within the framework of divine simplicity and unity, in contrast to Ashʿarite theology, which posits attributes as realities that inhere in but are not identical with the Essence. Ibn Rushd’s principal contribution lies in his consistent application of the demonstrative (burhānī) method and his development of the idea of harmonizing reason and revelation through a classification of levels of human understanding. Ibn Rushd’s thought remains highly relevant for strengthening inter-school dialogue, integrating science and religion, and advancing contemporary studies in Islamic philosophy.